Polyarthritis of Adult: Challenges in the Diagnosis - Yesmin, Sabrina (Bangladesh Journal of Medicine, 2024)
Diagnosing polyarthritis in adults poses considerable challenges due to the multifaceted nature of the disease and its symptoms. Polyarthritis involves inflammation in multiple joints simultaneously, often leading to severe pain, stiffness, and reduced mobility. The primary diagnostic challenge lies in the diverse aetiology of the condition, including rheumatoid arthritis, psoriatic arthritis, gout, and other autoimmune diseases, each requiring different management strategies. Complications in diagnosis arise from the overlapping clinical manifestations and the absence of a singular diagnostic test that can conclusively identify the underlying cause. Moreover, the sensitivity and specificity of available serological markers vary, and imaging findings can be similar across different types of polyarthritis. This complexity necessitates a multifactorial diagnostic approach combining clinical evaluation, laboratory testing, and advanced imaging techniques. This abstract highlights the importance of a tailored diagnostic strategy that accommodates the individual variations in disease presentation and progression, aiming to enhance diagnostic accuracy and optimize therapeutic outcomes. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 137